Ecologic study of influenza vaccination uptake and COVID-19 death rate in New York City - Ashley Moreland; Christina Gillezeau; Adriana Eugene; Naomi Alpert; Emanuela Taioli (BMC, 2022)
Abstract Background The aim of this ecological study was to assess the area-level relationship between cumulative death rate for COVID-19 and historic influenza vaccination uptake in the New York City population. Methods Predictors of COVID-19 death included self-reported influenza vaccination in 2017, as well as four CDC-defined risk factors of severe COVID-19 infection available at the ecological level, which were diabetes, asthma, BMI 30-100 (2 kg/m2) and hypertension, in addition to race and age (65 + years). Results After adjusting for potential confounders, for every one-unit increase in influenza vaccination uptake for each zip code area, the rate of COVID-19 deaths decreased by 5.17 per 100,000 residents (p < 0.0001). Conclusions Zip codes with a higher prevalence of influenza vaccination had lower rates of COVID-19 mortality, inciting the need to further explore the relationship between influenza vaccination uptake and COVID-19 mortality at the individual level.